(untitled) (Palíndromo, 2023)
This article analyzes the performance “2021: Spell to be invisible” (2019), performed by the artists Jota Mombaça and Michelle Mattiuzzi and, later, exhibited in 2021 at the 34th Bienal of São Paulo. The interpretation will start from Mombaça’s texts that reflect on the language of performance, the use of writing and the questions regarding the process of framing differences within the world of art. The argument is completed with testimonials from the artists themselves about the work and the way they understand their acting. In parallel, we bring the contribution of authors such as Michel Foucault, Judith Butler, Giorgio Agamben and Sílvio de Almeida to think about the place of racialized bodies in institutionalized environments, taking into account visibility policies and the right to opacity, a concept by Édouard Glissant that we approach the work of the artists. As final notes, we observe that the performance analyzed marks the tensions around the occupation of dissident and racialized bodies in spaces of power, which recurrently want them to be docile and controlled.